THE EFFECT OF SOWING DATES AND PLANTING DENSITIES ON THE EMERGENCE AND PLANT DENSITY OF SUGAR BEET - Choriyev Erali Olimovich; Xalikov Baxodir Meylikovich (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2026)
This article presents the data obtained on the effects of sowing dates and plant densities of sugar beet on its germination and plant density, along with the results of their analysis. It was found that when both varieties were sown 12–13 days later than the March 20–30 period, that is, between April 5–15, their germination occurred 3–4 days earlier. By the end of the growing period, the variety “Eldona” had 0.2–0.5% fewer plant losses compared to the variety “Sado.” The findings also show that sowing between April 5–15 instead of March 20–30 allows for preserving 0.1% to 0.3% more seedlings.